PENDAFTARAN JAMINAN FIDUSIA SEBAGAI PEMENUHAN ASAS PUBLISITAS - Supianto Supianto; Nanang Tri Budiman (Indonesian Journal of Law and Islamic Law (IJLIL), 2020)
Before the birth of the Fiduciary Guarantee Law (UUJF), the issue of fiduciary security registration was not an obligation, but with the birth of the UUJF, registration of fiduciary guarantees was a very crucial stage and had an impact on many aspects of the following law. Such explanation is also recognized in the General Elucidation of UUJF that one of the reasons fiduciary guarantees does not provide legal certainty, especially to fiduciary recipients, one of which is because the fiduciary guarantee is not registered. The fulfillment of the principle of publicity in fiduciary security is carried out by registering fiduciary security at the Fiduciary Registration Office. Regarding the request, the registration office will record the guarantee in the Fiduciary Register Book and will issue a Fiduciary Guarantee Certificate which has the order for Justice Based on Almighty God. The normalization of fiduciary security registration in UUJF is a legal norm that is compelling (dwingend recht). This can be seen through two aspects, namely the use of the word mandatory in UUJF as a command norm, and from the aspect of the legal principle of objects which are closed, so that the norm cannot be deviated. With regard to fiduciary security that is not registered, the creditor as the recipient of fiduciary does not receive the rights and benefits specified in the UUJF, including material rights, priority rights, executive rights, and application of criminal provisions.